Tinjauan Yuridis SEMA Nomor 2 Tahun 2023 Mengenai Larangan Perkawinan dari Agama yang Berbeda di Indonesia dan Dampak Hukumnya - R. Rizki; Ongko Surya; Kenny Cendana; Felix Salim (Fakultas Hukum, Universitas Warmadewa, 2025)
Interfaith marriage has become a controversial issue that causes legal emptiness and uncertainty within the Indonesian legal system. This is due to the legal conflict between the Marriage Law, which prohibits interfaith marriages, and the Population Administration Law, which allows interfaith marriages under the condition of a court decision. To resolve this issue, the Supreme Court issued Circular Letter Number 2 of 2023 on July 17, 2023. However, in practice, applications for the registration of interfaith marriages are still granted, as evidenced by the North Jakarta District Court Decision No. 423/Pdt.P/2023/PN Jkt.Utr on August 8, 2023. This study employs a normative juridical method with a qualitative, descriptive analytic approach, relying on secondary data sources including primary and secondary legal materials. Since SEMA holds a lower position in the hierarchy of regulations, beneath the Law, it is subject to the principle of